Conceptual aspect of the definition of the term soul as the category of theoretical psychology - Koval, Gennadiy (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2019)
The problematic of the categorical aspect of the term of the soul through the prism of the principle of systematicity (organization) has been reviewed in the article. The problematic of the place of the category of a soul in the categorical apparatus of theoretical psychology have been shown through the context of general categories of the structure of the human – an organism, an individual, an individuality, a personality, the I, the subject. The problematic of analysis and disclosure of the meaning load of the specified of categories which is due to the application of the principle of determinism to their analysis has been noted. The possibility of building a hierarchical range of categories as levels of concretization (organization) of a mental structure of the one by analogy with respect to such a range of levels of concretization (organization) of a living that have been shown. It has been noted that specifics for a range of levels of organization of a living one is its start with a unit of analysis of what is alive – an organism, also specific is its completion represented as a unit of development of a living form of life – a body. The conceptual filling of range of levels of an organization that is characteristic to a mental structure is appropriate of general categories of the structure human in accordance with the principle of systemicity has been proposed. The article also deals with the connection of the concept of a soul with categories that lie beyond the scope of psychological science per se, like philosophy. The necessity of the said action is justified by the historical context of the humanity’s literary and social practices that include the notion of the soul. The article concludes with the outline of the future direction for theoretical research of the outlined problematic aimed at making space for the notion of the soul in psychological science and the system of its concepts. Overall, the work is dedicated to the efforts of bringing more clarity to the use of the concept of the soul within the existing paradigm of psychology.